Morphology and colony development of stingless bees Lophotrigona canifrons (Hymenoptera: Apidae) - Md Salleh, Muhammad Firdaus (2016)
Lophotrigona canifrons was found that they have a potential to be commercialized in the future in order to fulfill the consumption of honey. This is because of L. canifrons can develop a big honey pot, they can supply a greater amount of honey compared to other commercialize stingless bees nowadays. Through this study, L. canifrons were being observe to study the morphology and to compare the temperature and relative humidity outside and inside the topping box. Other than that, the development of colony of L. canifrons were being observed. In this study, the data shows that there is no significant difference between the temperature inside the topping box and outside the topping box (df = 12 ; P-Value = 0.423 ; T-Value = -0.20) and relative humidity inside the topping is significantly higher than outside the topping box (df = 12 ; P-Value = 0.004 ; T-Value = 3.20). This shows that there is correlation between relative humidity towards the development of the colony of L. canifrons and the structure of involucrum becomes more complicated over the time passes.